2021
DOI: 10.1007/s11482-020-09906-2
|View full text |Cite
|
Sign up to set email alerts
|

Who Becomes Unhappy when Income Inequality Increases?

Abstract: Literature has established that, on a macroeconomic level, income inequality has a negative effect on average life satisfaction. An unresolved question is, however, which income groups are harmed by income inequality. In this paper we investigate this relationship at the microeconomic level combining national indicators of income inequality with individual data of life satisfaction from the World Values Survey for 39 countries over a period of 25 years. Tests on moderation by income category show that the Gini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
(77 reference statements)
1
7
0
Order By: Relevance
“…The weaker provision of the latter in more unequal countries impairs people's ability to convert resources into the kinds of lives that would satisfy them more as their incomes increase. This is consistent with Lous and Graafland's (2022) evidence, using data from the World Values Survey, that even those on the highest incomes see costs to life satisfaction as income inequality increases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The weaker provision of the latter in more unequal countries impairs people's ability to convert resources into the kinds of lives that would satisfy them more as their incomes increase. This is consistent with Lous and Graafland's (2022) evidence, using data from the World Values Survey, that even those on the highest incomes see costs to life satisfaction as income inequality increases.…”
Section: Discussionsupporting
confidence: 89%
“…Across many studies, greater income inequality has been associated with lower average wellbeing, whether wellbeing is measured as depression, anxiety, health, life expectancy, trust, or a number of other outcome variables (Lous & Graafland, 2022;Verme, 2011;Wilkinson & Pickett, 2009. Pickett and Wilkinson (2015) have argued that this association meets typical epidemiological criteria for causality: It is consistent across many datasets, dose-responsive, and not obviously the result of confounding variables.…”
Section: Introductionmentioning
confidence: 99%
“…There are differences in the family economic status of Chinese elderly people. We divided the family income of elderly people into ten equal parts, and considered the top 10 percent as the high-income group and the bottom 10 percent as the low-income group [47,48]. Then, we investigated the trends of financial support and informal care provision of adult children to their parents among the two groups from 2008 to 2018.…”
Section: The Trends Of Financial Support and Informal Care Provision ...mentioning
confidence: 99%
“…2022), we argue that these two contextual variables could have similar effects on workers’ job satisfaction and dignity. Previous studies have shown that economic inequality undermines an individual's general well‐being, happiness and satisfaction (Alesina et al., 2004; Delhey & Dragolov, 2014; Graafland & Lous, 2019; Lous & Graafland, 2022; Oishi et al., 2011; Tavor et al., 2017). Economic inequality also has an effect on people's lives across organizations (Amis et al., 2018; Bapuji et al., 2020; van Dijk et al., 2020).…”
Section: Introductionmentioning
confidence: 99%